2014
DOI: 10.1111/j.1532-950x.2014.12159.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Incidence and Risk Factors for Surgical Glove Perforation in Small Animal Surgery

Abstract: There is a high incidence of unrecognized glove perforations in small animal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
48
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(58 citation statements)
references
References 22 publications
8
48
2
Order By: Relevance
“…However, the frequency of perforations in our orthopedic and open soft tissue surgery (33–39%) were higher. These procedures were significantly more likely (3 times) to have glove perforations than minimally invasive surgery, in agreement with previous studies stating that increased invasiveness (open procedures) and sharp orthopedic equipment increases the risk of glove perforations …”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, the frequency of perforations in our orthopedic and open soft tissue surgery (33–39%) were higher. These procedures were significantly more likely (3 times) to have glove perforations than minimally invasive surgery, in agreement with previous studies stating that increased invasiveness (open procedures) and sharp orthopedic equipment increases the risk of glove perforations …”
Section: Discussionsupporting
confidence: 91%
“…This study reports the frequency of undetected glove perforations in equine surgery. The overall 27% frequency, with a 95% confidence interval of 22–33% captures the estimates of 22 and 26% from small animal surgery, as hypothesized . However, the frequency of perforations in our orthopedic and open soft tissue surgery (33–39%) were higher.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The overall incidence of postoperative glove perforations in our study was 18%. This is within the range of the incidence reported in other veterinary studies (10.2–26.2%) . These studies reported a similar increased risk for punctures in the nondominant hand, on gloves worn by the primary surgeon, and in surgeries of longer duration.…”
Section: Discussionsupporting
confidence: 87%
“…Surgeon‐based intraoperative glove contamination may be a result of glove puncture and bacterial migration from the surgeon's hand to the glove surface. The frequency of intraoperative glove puncture in veterinary medicine ranges from 10.2–26.2% …”
mentioning
confidence: 99%